PEMBELAJARAN SEJARAH LOKAL DI SEKOLAH PEDESAAN DAN VOKASI - Nur Fatah Abidin (Jurnal Pendidikan Sejarah Indonesia, 2020)
One of the problems of history learning in the rural and vocational schools lies in the gap between the learning objectives, which covers philosophical, normative-educative, and political purposes, and the students’ learning purposes that tend to be pragmatic. This paper seeks to construct a concept and practice of local history learning that accommodate those learning objectives for the rural and vocational schools. Through library research methods, the author formulates the concept of the practicality of history into a conceptual foundation for learning local history in rural and vocational schools. The practicality of history emphasizes the benefits of the learning history for the daily lives of students. Learning local history in rural schools is focused on analyzing and exploring local potential, according to what extent it can be useful to fulfill the basic needs of students. In vocational schools, local history learning is directed to strengthening students' skills to align with the concept of link and match. Practically, the local history learning in rural and vocational schools can be carried out in the form of project-based learning, for instance, Historical Project-based Learning.